PkM. PELATIAHAN DAN PENDAMPINGAN PUPLIKASI ILMIAH GURU DI SMA NEGERI 8 DENPASAR - I Made Suarta; I Komang Sukendra; I Nyoman Bagus Suweta Nugraha (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
Scientific publications have an important role for teachers, especially as a requirement for advancing their career path through promotion. However, many teachers face obstacles in writing and publishing scientific papers independently. This Community Service Program (PkM) aims to increase the knowledge and skills of teachers at SMA Negeri 8 Denpasar in scientific publications. The methods used include socialization, training, application of technology, mentoring and evaluation. This activity involves all teachers as participants. The results of the activity showed an increase in teacher motivation and ability in writing scientific articles, especially those based on classroom action research and best practices. Teachers are able to compose articles according to the template of the targeted national ISSN journal. Thus, this program succeeded in increasing teacher competence in scientific publications while supporting their professionalism. Through this PkM program, teachers at SMA Negeri 8 Denpasar understand and are able to compose scientific articles based on written work, such as classroom action research or best practices, according to the template of the targeted national journal. This program has also succeeded in improving the quality of teachers' human resources (HR) in scientific literacy.